Association of sense of coherence and periodontal disease severity, in two cross‐sectional studies - Wahlin, Åsa; Lindmark, Ulrika; Norderyd, Ola (International journal of dental hygiene, 2024)
Objectives To investigate the association between the individuals' level of sense of coherence (SOC) and periodontal disease severity. Methods The study populations originated from two stratified cross‐sectional random samples of residents in a medium‐sized Swedish city in 2003 and 2013, respectively. The final samples constituted 491 individuals in 2003 and 538 individuals in 2013. The samples were classified into three groups according to the severity of periodontitis (no/minor, moderate and severe). The 13‐item Swedish version of Antonovsky's “Orientation to life” questionnaire, measuring the individual's SOC, was filled out. Descriptive statistics were performed as well as multinomial logistic regression analysis. Dependent variable was the severity of periodontal disease and independent variables, age in years, presently smoking and education at university level. Results In the multinomial regression analysis, smoking, age, and total SOC score were significantly associated with severe periodontitis at both examinations. The strongest predictor of severe periodontal disease was smoking. The total SOC score did not differ between the examinations, but there was a statistically significant difference in two of the SOC dimensions, manageability (lower), and comprehensibility (higher), over time. Conclusions Individuals with severe periodontitis had significantly lower SOC compared to subjects periodontally having no/minor periodontal disease. Smoking was the strongest overall predictor of having severe periodontitis.